Evaluation Report on Accelerated Rural Water Supply Programme - Planning Commission (Planning Commission, 1996)
The Accelerated Rural Water Supply Programme (ARWSP) is being implemented by the Central Government since 1972-73 with the objective of supplementing the efforts of the State Governments in providing adeguate safe drinking water to the rural population. At the instance of the Planning Commission, the Programme Evaluation Organisation undertook the study to evaluate the performance, implementation and impact of the programme. The study was also reguired to address the issues relating to: people's awareness about safe drinking water and sanitation; their participation in implementation, operation and maintenance of facilities; sustainability and dependability of water sources and the re-emergence of no-source villages.
Programme Evaluation Organisation Planning Commission Govt. of India